ORAL HYGIENE INDEX-SIMPLIFIED IN MENTALLY DISORDERED PATIENTS AT SAMBANG LIHUM PSYCHIATRIC HOSPITAL - Juli Harnida Purwaningayu; Farida Auliyani; Ramadhani Fitria Nisa; Ghina Rahmatika; Norhasanah Norhasanah (FKG ULM, 2025)
Background: Oral hygiene is a risk factor for oral health, particularly in individuals with mental disorders. The prevalence of oral health issues in Indonesian society has increased from 25.9% to 57.6%. The Dental Hygiene Index Simplified (OHI-S) is a clinical instrument employed to assess dental hygiene status. According to the World Health Organization, approximately 24 million individuals worldwide are afflicted with schizophrenia, 35 million individuals are afflicted with melancholy, 60 million individuals have bipolar disorder, and 47.5 million individuals have dementia. It was shown that the percentage of mental disorders increased from 1.7% in 2013 to 7% in 2018. Objective: To ascertain the oral hygiene status of patients with mental disorders in the inpatient chamber of Sambang Lihum Mental Hospital by utilizing the Oral Hygiene Index-Simplified (OHI-S). Methods: This study was a quantitative descriptive study using a cross-sectional design. The sampling was carried out by purposive sampling based on inclusion and exclusion criteria. The total sample for this study was 54 individuals. Results: 29 people (53.70%) of the patients examined had a poor OHIS category. The OHIS score for mental patients was inadequate in all age categories. Men had a score of 3.2 (poor), while women had a score of 2.7 (fair). The mental patients' aggregate OHIS score was 3.10, which is classified as